PERKEMBANGAN TELUR AMERIANNA CARINATA (H. ADAMS) - RISTIYANTI M. MARWOTO (BERITA BIOLOGI, 1986)
RISTIYANTI M. MARWOTO. 1986. The egg development on .Amerianna carinata (H. Adams). Berita Biologi 3(4): 178 - 180. An attempt was made to observe the egg development on 14 of A. carinata snails collected from a pond near the palace at the Bogor Botanical Gardens. It was found that after being incubated for 2-4 days, many of the snails laid 7 capsules, each capsule containing 3 to 27 eggs. The diameter of the capsule was between 4-7 mm, while the egg was about 0,3 mm. The embryos completed their development within 7 days and it was then followed by the egg batched in 1 to 2 days.